Impelementasi Pembisaan Membaca Juz Amma Untuk Membentuk Karakter Religius Peserta Didik di Madrasah Aliyah Al-Kholafiyah Tekung Lumajang - Arifin, Syamsul; Ikrom, Fahmi (LP3M Universitas Islam Zainul Hasan Genggong, 2022)
This research is motivated by the dryness of religious character among teenagers caused by the rapid development of technology as it is today which has an impact on teenagers they prefer to play gadgets, the impact is that teenagers are less skilled in reading the Qur'an, there are even minorities of those who have not. able to read the Qur'an properly and correctly according to the rules of recitation. As an effort to shape the religious character of students in this day and age, MA AL-kholafiyah carries out the habit of reading Juz Amma. The focus of this research is to find out the implementation of the habit of reading Juz Amma to shape the religious character of students at MA Al-Kholafiyah, the supporting and inhibiting factors and what the implications are. The method used in this research is descriptive qualitative method. The results of data analysis in the form of exposure to the situation under study and presented in the form of a narrative description. In collecting data, researchers used interview, observation and documentation techniques